Odpowiedź :
przypuszczam ze to tak
(5 3/11 -2 1/11)* pierwiastek3(-8)
3 2/11*(-2)=-6 4/11
ale moze byc tez tak
5 3/11 -2 1/11* pierwiastek3(-8)
5 3/11+4 2/11=9 5/11
nie wiadomo czy ma byc nawias czy najpierw mnozenie wiec masz tak i tak
pozdro
(5 3/11 -2 1/11)* pierwiastek3(-8)
3 2/11*(-2)=-6 4/11
ale moze byc tez tak
5 3/11 -2 1/11* pierwiastek3(-8)
5 3/11+4 2/11=9 5/11
nie wiadomo czy ma byc nawias czy najpierw mnozenie wiec masz tak i tak
pozdro
5 3/11 -2 1/11 *∛-8=5 3/11- 2 1/11 *(-2)= 5 3/11 +4 2/11=9 5/11
(3/4-2/3)*(2/3-1/2)= (9/12-8/12)(4/6-3/6)=1/12*1/6=1/72
(2⁶)⁷/8¹³=2⁴²/(2³)¹³=2⁴²/2³⁹=2³=8
(3/4-2/3)*(2/3-1/2)= (9/12-8/12)(4/6-3/6)=1/12*1/6=1/72
(2⁶)⁷/8¹³=2⁴²/(2³)¹³=2⁴²/2³⁹=2³=8